Repair, restitution, compensation: The Cultural Heritage of the nations - Belevan-McBride, Harry (2022)
On July 28, 2021, international news agencies announced that, on the occasion of the Iraqi Prime Minister's official visit to Washington, the United States had agreed to return 17,000 archaeological pieces of various kinds to his country, a return process known in UNESCO for decades as "restitution of looted cultural property". The objects were returned by Cornell University and the Evangelical Christian Church's Washington Museum of the Bible. These are tablets and seals from some of the oldest civilizations in the world, including objects from the lost city of Irisagrig, the existence of which was only known for the first time in 2003, when a shipment of illegal trafficking in icons was confiscated that mention that human settlement. That day in July these treasures were unveiled at the headquarters of the Iraqi Ministry of Culture.